Academia and Practitioner Perspectives on Competencies Required for Technical and Vocational Education Students in Malaysia: A Comparison with The ASTD WLP Competency Model. (13th May 2015) - Salleh, Kahirol Mohd; Sulaiman, Nor Lisa; Mohamad, Mimi Mohaffyza; Sern, Lai Chee
Abstract: The aim of this paper is to explore the competencies perceived important by academics and practitioners in order to prepared graduates for workforce environments. Moreover, this paper examines the competencies that are perceived to be important by university faculty and practitioners in Malaysia. This paper is a qualitative study. Therefore, an interview has been used as an instrument to gather the data. Interviews with university faculty and workforce practitioners were thematically analyzed to compare and contrast their perspective on competencies. Additionally, this paper also examines the relationship between competencies and organization performance. Academia and practitioners from Malaysia were identified and a set of electronic interviews questionnaires were sent through e-mail to them to be answered. Findings show that both academic faculty and workforce practitioners agree that graduates need to possess the necessary competencies before entering the workplace. It appears that most workplaces need graduates who are highly motivated and willing to learn within the organization. Additionally, the practitioners urge that practical training or internships are be an important element that has to be embedded into programs offered in universities.